Merjenje velikosti medvretenčne ploščice s pomočjo antropometrijske metode - Turk, Zmago (Zdravniški vestnik, 2004)
Background. There is a positive correlation between the size of intervertebral disc (IVD) and the incidence of Low Back Pain (LBP). Columbini evaluated the size of IVD anthropometricaly but how this measurement correlates with radiologic measurements of IVD square size is steel unknown. Objective. The aim of the study was to search for non-invasive method and cheap and fast evaluation of IVD size with the modification of Columbini's antropometric formula. Materials and methods. The measurements (anthropometrics, X-ray, CT with range of interest measurement ROI) were done on 40 bus-drivers. The realibility test was done on 65 bus-drivers. Results. CT measurement of the size of the intervertebral disc was done using ROI (Range of Interest). Using the statistical analysis based on linear regression, correlation, curve fitting and realibility the author made the modification of Columbini's formula. The incidence of Low Back Pain was statistically significantly higher in people with smaller IVD, particularly in men. Conclusions. With the Columbini's method of anthropometric measurement of the size of IVD modified by Turk it is possible to make the right measurement prognosis in 89% of cases. Consequently, there is no need to use invasive and costly diagnostic radiologic methods.
Keywords: Anthropometry; Antropometrija; Back pain; Bolečina v hrbtu; Intervertebral disk; Medvretenčna ploščica; Tomografija, radiografska, računalniška; Tomography, X-ray computed